2016
DOI: 10.1589/jpts.28.407
|View full text |Cite
|
Sign up to set email alerts
|

Are rate of perceived exertion and feelings of pleasure/displeasure modified in elderly women undergoing 8 week of strength training of prescribe intensity?

Abstract: [Purpose] The aim of the present study was to verify the rate of perceived exertion and feelings of pleasure/displeasure in elderly women, who did normally perform physical exercises, following eight weeks of strength training in a constant routine. [Subjects and Methods] Eleven sedentary women were subjected to anthropometric assessment. The maximum load (100%) for each used in this study was determined by performing a test to determined the 1RM for each of them according to the protocol of Fatouros et al. an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Strength training studies on pleasure are still inconclusive [7,11,12,31,32]. In a study involving trained men, Portugal et al [12] observed a decrease in pleasure only when the high-intensity (80% 1RM) group was compared with the control group (without exercise).…”
Section: Discussionmentioning
confidence: 99%
“…Strength training studies on pleasure are still inconclusive [7,11,12,31,32]. In a study involving trained men, Portugal et al [12] observed a decrease in pleasure only when the high-intensity (80% 1RM) group was compared with the control group (without exercise).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study that analyzed the acute responses of pleasure and RPE in two different methods (traditional vs. cluster-set). In addition, there are still few studies that analyzed the pleasure responses in the RT and most of them investigated the effect of the intensity of the training on this variable (Benites, Alves, Ferreira, Follador, & da Silva, 2016;Elsangedy, Krinski, da Silva Machado, Okano, & da Silva, 2016;Portugal et al, 2015). However, the configuration of different trainings, due to the manipulation of other acute training variables, besides the intensity, might modify the psychophysiological responses during the resistance training, more specifically, the rest interval.…”
Section: Discussionmentioning
confidence: 99%